Penerapan Data Mining Untuk Menentukan Tingkat Ketersedian Minimum Atas Material On-Hand Pada Pt. Dhl Supply - Bambang Hermanto; Nissan Situmeang (Jurnal SIGMA, 2019)
Mining data or efforts to explore valuable information and knowledge in the database a very large one is called data mining or Knowledge Discovery in Database abbreviated KDD. One of the most popular algorithm in data mining techniques is the Apriori algorithm. Whereas in the discovery Patterns of relationship combinations between itemssets are used Association Rules. Data Mining has been implemented in various fields, including business or trade, education, and telecommunications. In the business sector, for example, the results of data mining implementation using Apriori algorithms can help business people in decision-making policies what is related to inventory. For example the importance of the inventory system at a company and what types of goods are the top priority that must be in stock to anticipate void of goods. Because the lack of stock can affect consumer service and income company. Therefore, the availability of various types of materials or products in a company as one of the food suppliers, is absolutely necessary to support the smooth distribution to consumers, so that the activity customer service goes well. Keywords: Data Mining, Association Rules, Apriori Algorithms, Inventory Level.